Experimental investigations of a common rail direct injection diesel engine using biodiesel blends in reactivity controlled compression ignition mode / Teoh Yew Heng - Teoh, Yew Heng (2016)

(untitled)
In recent years, rapid growth in population, development, and industrialization have led to a high demand for energy worldwide. Biofuels from bio-based products can be considered an alternative to fossil fuels used in the transport sector. However, the use of biodiesel in conventional diesel combustion engines has usually caused lower thermal efficiency and higher in specific fuel consumption. Using alternative fuels and switching to promising combustion technologies such as low temperature combustion (LTC) are reliable approaches to address this issue. This research aims to use biofuels as an alternative energy source for engines operating in reactivity controlled compression ignition (RCCI) dual-fuel combustion mode. In the first stage, a test cell system was developed, which consisted of a single cylinder diesel engine, dynamometer and combustion analyzer system. This was followed by the extensive conversion and integration of the high pressure common-rail injection to the test engine for providing high degree of flexibility in the control of injection parameters. In the second stage, an experimental investigation to study the effects of palm and Jatropha biodiesel fuels on the engine performance, emissions, and combustion characteristics of the converted engine was performed under different load operations. The test fuels included a conventional diesel fuel and eight different blends of palm and Jatropha biodiesel fuels. During the third stage, parametric studies dealing with injection timing and exhaust gas recirculation (EGR) variation by using neat palm biodiesel were performed and compared with baseline diesel. In the final stage, the effects of diesel/ biodiesel strategies on dual-fuel combustion were investigated. This dual-fuel combustion mode proposes port fuel injection of gasoline and direct injection of diesel/ biodiesel fuel with rapid in-cylinder fuel blending. Engine performance, emissions, and cylinder pressure trace were sampled and analyzed under different experiment schemes. The results indicated that the in-house iv developed ECU is capable of real-time control and monitoring of the injection parameters. The second stage experimental results revealed that the biodiesel blended fuels had a significant influence on the brake specific fuel consumption (BSFC) at all the engine load conditions examined. In general, the use of neat and blends of biodiesel resulted in a reduction in brake specific nitrogen oxide (BSNOx), brake specific carbon monoxide (BSCO), smoke emissions, shorter ignition delay (ID), and shorter combustion duration regardless of the load conditions. Besides, the third stage experimental results indicated that both the injection timing and EGR variation had a prominent effect on the engine performance, emissions and combustion characteristics with baseline diesel and neat biodiesel operation. Based on the highest brake thermal efficiency (BTE) and the reasonable NOx level, thus the optimum injection timing is found to be 11°BTDC for both the baseline diesel and biodiesel operation. Introduction of EGR has effectively reduced the NOx emissions, but has increased the smoke emissions. In the last stage experiment, the results showed that the engine operating under RCCI dual-fuel combustion mode could achieve high efficiency with near zero NOx and smoke emissions.